2014
DOI: 10.1117/12.2074525
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of a photonic crystal fiber with cholesteric liquid crystal and blue phase

Abstract: Photonic crystal fibers (PCF) have been selectively filled with a cholesteric liquid crystal (ChLC) with special interest in the blue phase (BP) of the liquid crystal. It has been observed thermal tuning of the guided light in the visible region. A dramatically enhance appears when the phase of the liquid crystal changes from cholesteric to blue phase I (BPI). When a thermal range of the blue phase I is achieved, no changes are observed while increasing temperature from BPI through BPII and to the isotropic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…As is known, various ordered phases of LCs such as nematic phase, smectic phase, chiral nematic phase have been used for fabricating liquid crystalline optical fibres, but nematic LCs are mostly investigated due to their extraordinarily non-linear optical and electrooptical responses [129]. However, there still exist two main difficulties and limitations upon application of nematic LCs in the ordered state, that is, the strong scattering loss and strict requirements for molecular alignment.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 99%
“…As is known, various ordered phases of LCs such as nematic phase, smectic phase, chiral nematic phase have been used for fabricating liquid crystalline optical fibres, but nematic LCs are mostly investigated due to their extraordinarily non-linear optical and electrooptical responses [129]. However, there still exist two main difficulties and limitations upon application of nematic LCs in the ordered state, that is, the strong scattering loss and strict requirements for molecular alignment.…”
Section: Fibre Arrays Filled With Blue Phase Liquid Crystalsmentioning
confidence: 99%
“…Therefore, it is easy to observe and use BP phase in many configurations. In the paper [23] the thermal tuning of the guided light in photonic crystal fiber filled with BPLC was observed. M. Wahle et al [24] shown experimental and modal analyses of electric field applied on photonic crystal fiber filled with BPLC.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published scientific reports devoted to PLCFs describe potential applications of PCFs infiltrated with nematic LCs [2][3][4][5][6][7][8][9]. However, other types of LCs, such as chiral smectic C LCs (SmC*), with their ferroelectric properties (FLCs) [10,11], or the LC blue phase exhibiting a three-dimensional double-twist structure [12][13][14], have also been considered as suitable materials for infiltrating the PCF structure. The most significant factor of the prospective PLCF-based optical systems is their rapid electro-optical response.…”
Section: Introductionmentioning
confidence: 99%